Identifying Phonological Interference of Indonesian Multilingual Learners at Reading Test with Genre-Based Approach Perspective and AI Tool - Ficayuma, Lina Aris (CV Infinite Corporation, 2024)
The present study is succinct summary which aims to identify factors of phonological cross linguistic influence faced by students of secondary bilingual boarding school, an educational institution that utilizes English and Arabic as medium of instruction. The subjects of this research are cross-ethnic students with diverse linguistic backgrounds, including Indonesian, Javanese, Madurese, Sundanese, Arabic, and English as their first language (henceforth, L1) to fifth languages (henceforth, L5). This research adopted qualitative descriptive research design and employed a purposive sampling method. 23 Students were selected as informants for this research, representing 25% of the total social situation in eleventh grade. Content analysis, reading test, and interview were used as data collection techniques. The test analysis result conducted using AI tools (ELSA Speak application) to measure pronunciation errors, intonation, and fluency in English. The data analysis technique followed the steps proposed by Miles et al., (2014), which include the data collection, data reduction, data display, and conclusion. The findings of this research revealed that Phonological Cross Linguistic Influence is attributed to two primary factors, technical factors and fundamental factors. Technical factors consist of: (1) Differences in the sound system of the languages, (2) Similarity of sounds between two languages. On the other hand, fundamental factors comprise: (1) Student’s linguistic background, (2) Student’s motivation, (3) Language habits/ attitudes (lack of practice and intensity of native language usage), (4) Learning environment (teacher’s lack of creativity and learning’s lack of program evaluation). Furthermore, the result reading test of 23 participants (SLA: Indigenous, Indonesia, Arabic, and English) using ELSA Speak show 9 different phonological interference of 28 vowels /??/; /a?/; /æ/; /??/; /?/; /a?/; /??/; /?:/; /??/ which 65% for L3, and 75% for L4. While 5 consonant /?/; /?/; /ð/; /?/; /?/ which 78% for L3, and 92% for L4. This difficulty was faced due to grammatical limitation, structure in building conversation, and accuracy detection. Implication of this study for EFL Materials, English curriculum policy makers and educators to be aware and emphasizing vocabularies which need to be emphasized Indonesians’ learners.